Hammering Techniques in Greek and Roman Jewellery and Toreutics - Treister (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This book traces the development of hammering techniques in Greek, Roman and related (e.g. Graeco-Scythian) jewellery and toreutics based on the analysis of ancient tools used for manufacture of hammered metalwork, primarily punches and matrices with figural designs, and actual finds of metalwork and jewellery. The book offers essays on metalworkers' tools from Mycenean Greece until the Late Roman Period. It includes chapters on different categories of hammered metalwork in the corresponding periods and Excursus about particular matrices or punches and hoards of toreutics. Bringing together the tools of metalworkers and actual objects manufactured with them opens new perspectives on chronological and cultural attribution of ancient jewellery and toreutics and illuminates the role of mass production and artistic creativity in ancient history. The book is illustrated with 133 photographs.